Initial Experience with Simple Oncoplastic Breast Conserving Surgery in Nepal: A Case Report - Singh, Yogendra P; Khanal, Suman (Journal of Institute of Medicine Nepal, 2020)
Oncoplastic breast conserving surgery is increasingly used in the management of early breast cancer. Though its use in Nepal is increasing, it is still under-utilized. We present a case of upper outer quadrant early breast cancer located away from nipple-areola complex managed with radial ellipse segmentectomy 10 years back and under regular follow up. We recommend its usage in upper outer quadrant lesions because of its simplicity, access for sentinel lymph node biopsy and good cosmetic outcome.